2015
DOI: 10.6002/ect.mesot2014.p122
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-Access Kidney Transplant

Abstract: Objectives: Minimal-access kidney transplant is not a new approach, however this approach is a good option for obese patients because access is difficult and often associated with wound complications and prolonged recovery. Materials and Methods: Minimal-access kidney transplant uses an inguinal incision that is placed 4-6 cm above the pubic bone that extends to 2.5-cm lateral to the mid-inguinal point. Once the skin and subcutaneous tissues are opened, the external oblique is split in the same direction as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the literature, MIS offers the advantages of cosmetic effect, less postoperative pain, fewer infections, early postoperative mobilization, a shorter recovery period, shorter hospitalization, reduced anesthetic risk and consequently a reduction in postoperative thromboembolic, respiratory, and metabolic complications. [ 11 12 ] Of course, MIKT also showed beneficial effects on postoperative pain, analgesia, recovery, and complication. [ 4 13 ] Øyen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, MIS offers the advantages of cosmetic effect, less postoperative pain, fewer infections, early postoperative mobilization, a shorter recovery period, shorter hospitalization, reduced anesthetic risk and consequently a reduction in postoperative thromboembolic, respiratory, and metabolic complications. [ 11 12 ] Of course, MIKT also showed beneficial effects on postoperative pain, analgesia, recovery, and complication. [ 4 13 ] Øyen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inflammatory cytokines accumulation leads to excessive reactive oxygen species (ROS), such as O2⋅- and ⋅OH ultimately contributes to IF/TA formation [ 12 , 16 ]. Some preclinical studies have shown that biopsy samples with CAD experience increased oxidative stress [ 17 ]. During the chronic IF/TA of renal allograft pathogenesis, the accumulation of ROS triggers the transdifferentiation of tubular epithelial cells [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in ammatory cytokines accumulation leads to the excessive reactive oxygen species (ROS), such as O2⋅-and ⋅OH, ultimately contributes to IF/TA formation 12,16 . Some preclinical studies have shown that biopsy samples with CAD experience increased oxidative stress 17 . During the chronic IF/TA of renal allograft pathogenesis, the accumulation of ROS triggers the transdifferentiation of tubular epithelial cells 18,19 .…”
Section: Introductionmentioning
confidence: 99%